Usability and usefulness of “smart indetect” for diabetic foot ulcer prevention - Taryudi, Taryudi; Lindayani, Linlin; Rif'an, Muhammad (Intelektual Pustaka Media Utama, 2024)
The utilization of the smart detection application has the potential to mitigate the incidence of decubitus ulcer infection. Smart InDetect incorporates artificial intelligence technology and is based on the internet of things and has the ability to detect the likelihood of infection and provide information regarding the proper management of wounds, as well as the care and treatment of infections. The objective of this study is to assess the usability, usefulness, and perceived satisfaction of potential users of the program. The present study employs a quantitative research methodology, utilizing a sample size of 30 participants. The findings of the research on usability and usefulness testing yielded an efficacy rate of 89% and 88.89% respectively, along with an average satisfaction score of 4.14 on a 5-point scale. Users perceive this program as both useful and efficient in its usability, particularly in relation to its ability to detect the risk of infection.